SPATIAL DISTRIBUTION OF SOIL AVAILABLE NUTRIENTS IN THE POTATO GROWING POCKETS OF BANASKANTHA DISTRICT OF ARID GUJARAT - Kumar, Mahesh; Jatav, Mukesh Kumar; Panwar, Navratan; Pandey, Chandra Bhushan; Chauhan, Jagdish (Potato Journal, 2016)
Abstract A study on spatial variability in available soil nutrient i.e organic carbon (OC), available P, K and DTPA extractable micronutrients (Zn, Cu, Mn & Fe) was carried out during 2011-2012. About 110 geo referenced surface soil samples were collected from potato growing area of Deesa tehsil of Banaskantha district (Gujarat state) using GPS (Global positioning system). The maps showing the spatial variability of major and micronutrients were generated using GIS software (Arc GIS-9.3). The organic carbon (OC) ranged from 0.18 to 0.80 % with mean value 0.38 % reflected poor N fertility of these soils. About 30% samples rated high (>103 kg P2O5 / ha), 52% medium (51-103 kg P2O5 / ha) samples and 18 % low in available phosphorus (>51 kg P2O5 / ha) for potato cultivation. While 77 % samples were rated low (<285 kg K2O / ha), 15% medium (285-407 kg K2O / ha) and 8 % rated high (>407 kg K2O / ha) in available K. With respect to micro-nutrients 40, 32 and 7 % soil samples were found deficient in zinc, iron and Cu, respectively. The corresponding values for different nutrients/parameters Â like OC, P, K, Fe, Zn, Mn, Cu and pH were linked with the respective sampling points and interpolation maps for each nutrient was generated in GIS using IDW technique. The map on spatial variability of OC showed that 95.0 and 5.0 per cent area was in the range of 0.10-0.50% and >0.50% respectively. About 65.10 % area was medium in available phosphorus and 27.30 % area was high in phosphorus whereas, 91.34% area was deficient in available K. Similarly 34.0, 29.8 and 3.3 % area was classified as deficient in Zn, Fe and Cu, respectively. These spatial variability maps clearly showed the specific locales of the pockets where attention is required with respect to management of major and micronutrients.Â